4-Nitroaniline Degradation by TiO2 Catalyst Doping with Manganese. (28th June 2015) - Zheng, Kai; Zhang, Tong-chao; Lin, Pin; Han, Yu-hua; Li, Hong-yi; Ji, Ren-jie; Zhang, Hai-yun
Abstract : Stainless steel anode covered with layer film of TiO2 doped with manganese was utilized to decompose 4-nitroaniline in rectangular borosilicate glass reactor, while stainless steel mesh was chosen as cathode; the anode and cathode were connected to the direct-current power; meantime two 60 W ( λ max = 365 nm) UV lamps were used as light source. The microstructures on TiO2 before and after being doped with manganese were analyzed by energy disperse X-ray (EDX) and X-ray diffraction (XRD). The performance of degradation of 4-nitroaniline was evaluated by analyzing cracking ratio of 4-nitroaniline ring, the chemical oxygen demand (COD), and total organic carbon (TOC) in remaining solution. Monitored parameters during all the photocatalytic reaction including dissolved oxygen, direct voltage, and radiation dosage of ultraviolet rays were investigated. When dissolved oxygen concentration, direct voltage, and radiation dosage of ultraviolet rays were, respectively, equivalent to 9 mg/L, 24 V, and 1200 μ W/cm 2, the degradation ratio of 4-nitroaniline reached maximum. The experimental results indicated that cracking ratio of 4-nitroaniline ring and the removal ratio of COD and TOC were, respectively, more than 99%, 85%, and 80% when reaction was run for 10 hours. The values of COD and TOC were, respectively, less than 16 mg/L and 8 mg/L while the experiment was finished.